Torsion of the gravid uterus: A rare cause of abdominal pain - Mangirish, R Dhaimode; Deepa, B Karmali; Ajit, A Nagarsenkar; Roy, M Menezes; Guruprasad, P Pednekar (Indian Journal of Case Reports, 2020)
Uterine torsion in pregnancy is a rare clinical entity with a non-specific clinical presentation. Here, we present a case of uterine torsion,which was diagnosed at laparotomy done for the lower segment cesarean section (LSCS) in a case of central placenta previa with thefetus in transverse lie. At 36.4 weeks period of gestation, the patient complained of severe left-sided abdominal pain which was notsuggestive of labor. This abdominal pain was refractory to analgesics. Emergency LSCS was done which confirmed uterine torsion aswell as anterior sacculation.